Impact of social network marketing and customer engagement towards customers’ online purchase intention related to travel agency / Mohamad Nazmi Nordin - Nordin, Mohamad Nazmi (Faculty of Business and Management, 2019)
The main objective of this research is to determine the impact of social network marketing and customer engagement towards customers’ online purchase intention related to travel agency. This research is to study whether there are any relationships between social network marketing and customer engagement towards customers’ online purchase intention. This research was conducted within Kuala Lumpur by distributing 132 questionnaires to individuals that have been using social networking sites related to travel agency. The sampling technique used was the non-probability sampling which was the convenience sampling. The result of the findings showed that one of the independent variables has significant relationship with dependent variable, while another independent variable has no significant relationship. As for the most influencial impact towards customers’ online purchase intention related to travel agency is the customer engagement.